Perbanyakan Tunas Mikro Pisang Rajabulu (Musa AAB Group) dengan Eksplan Anakan dan Jantung - Ernawati, Andri; Purwito, Agus; Pasaribu, J. M. (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Research on micropropagation of banana cv. Rajabulu (Musa AAB Group) was undertaken.  On initiation stage,  sucker  was best used as explant during rainy season on solid medium containing 7 mg/l BAP + 3 mg/l IAA and average microshoots was 7 shoots/bottle. While  inflorescence as explant was best for initiation during dry season on solid medium containing 9 mg/l BAP + 1 mg/l IAA and average microshoots was 18 shoots/bottle.  On multiplication stage, sucker produced microshoot on medium containing 4.5 mg/l BAP + 1.0 mg/l kinetin (2.9 shoots).  While inflorescense produced microshoot on medium containing 6.0 mg/l IAA + 2.0 mg/l BAP (2.4 shoots).  Acclimatization of plantlets produced from sucker and inflorescense was best on medium of compost 75% + soil 25%.   Key words: micropropagation, sucker, inflorescense,  banana Rajabulu  (Musa AAB Group)